Offer for alumni to participate in UMPSA Protege programme - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
PEKAN, 2 August 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is now opening opportunities for university alumni to gain experience serving in this university through the UMPSA Perdana Protege Fellowship Programme.